Numerical Simulation of a Mechanically Stacked GaAs/Ge Solar Cell - Enayat Taghavi Moghaddam, S.; Mehrdad Kankanani, S. (Engineering, Technology & Applied Science Research, 2017)
In this paper, GaAs and Ge solar cells have been studied and simulated separately and the inner characteristics of each have been calculated including the energy band structure, the internal field, carrier density distribution in the equilibrium condition (dark condition) and the voltage-current curve in the sun exposure with the output power of each one. Finally, the output power of these two mechanically stacked cells is achieved. Drift-diffusion model have been used for simulation that solved with numerically method and Gummel algorithm. In this simulation, the final cells exposed to sun light in a standard AM 1.5 G conditions and temperatures are 300° K. The efficiency of the proposed structure is 9.47%. The analytical results are compared with results of numerical simulations and the accuracy of the method used is shown.